Assessing the appropriateness of the management of gastro-oesophageal reflux in Australian children: a population-based sample survey - Gaston Arnolda (Nature Portfolio, 2021)
Abstract Gastro-oesophageal reflux (GOR) is a common physiological state in infants and young children, with gastro-oesophageal reflux disease (GORD) its pathological manifestation. Management of GOR/GORD requires elimination of possible underlying causes, parental reassurance, modification of feeding and symptom mitigation, monitoring, and referral to paediatricians if warning signs are present. Published clinical practice guidelines (CPGs) seek to support clinicians and improve management. This study aimed to measure the proportion of Australian GOR/GORD paediatric care that was in line with CPG recommendations. National and international CPGs for GOR/GORD were systematically identified and candidate indicators extracted; a Delphi process selected 32 indicators relevant to Australian paediatric care in 2012 and 2013. Medical records were identified in General Practices, the offices of general paediatricians, Emergency Departments and inpatient settings. Adherence to indicators was assessed by nine trained paediatric nurses undertaking retrospective medical record review. Medical records were reviewed in 115 healthcare sites; identifying 285 children, three-quarters aged < 1 year, who had 359 visits for management of GOR/GORD; 2250 eligible indicator assessments were performed. Estimated adherence rates are reported for 21 indicators with ≥ 25 assessments. Five indicators recommending differential diagnostic tests (e.g., urinalysis) for infants presenting with recurrent regurgitation and poor weight gain had ~ 10% adherence; conversely, avoidance of unrecommended tests (e.g., barium swallow and meal) was high (99.8% adherence: 95% CI 97.0–100). Avoidance of prescription of acid-suppression medication for infants at the first presentation was higher if they were healthy and thriving (86.9% adherence: 95% CI 86.0–96.8), intermediate if they had feeding refusal (73.1%: 95% CI 56.0–86.3) and lower if they presented with irritability and unexplained crying (58.8%: 95% CI 28.2–85.0). A guideline targeting Australian health professionals caring for infants and children with GOR/GORD is warranted, highlighting the importance of differential diagnostic testing and avoidance of acid-suppression medication in infants.